Multinucleation resets human macrophages for specialized functions at the expense of their identity. (4th January 2023) - Ahmadzadeh, Kourosh; Pereira, Marie; Vanoppen, Margot; Bernaerts, Eline; Ko, Jeong‐Hun; Mitera, Tania; Maksoudian, Christy; Manshian, Bella B; Soenen, Stefaan; Rose, Carlos D; Matthys, Patrick; Wouters, Carine; et al.
Abstract: Macrophages undergo plasma membrane fusion and cell multinucleation to form multinucleated giant cells (MGCs) such as osteoclasts in bone, Langhans giant cells (LGCs) as part of granulomas or foreign‐body giant cells (FBGCs) in reaction to exogenous material. How multinucleation per se contributes to functional specialization of mature mononuclear macrophages remains poorly understood in humans. Here, we integrate comparative transcriptomics with functional assays in purified mature mononuclear and multinucleated human osteoclasts, LGCs and FBGCs. Strikingly, in all three types of MGCs, multinucleation causes a pronounced downregulation of macrophage identity. We show enhanced lysosome‐mediated intracellular iron homeostasis promoting MGC formation. The transition from mononuclear to multinuclear state is accompanied by cell specialization specific to each polykaryon. Enhanced phagocytic and mitochondrial function associate with FBGCs and osteoclasts, respectively. Moreover, human LGCs preferentially express B7‐H3 (CD276) and can form granuloma‐like clusters in vitro, suggesting that their multinucleation potentiates T cell activation. These findings demonstrate how cell–cell fusion and multinucleation reset human macrophage identity as part of an advanced maturation step that confers MGC‐specific functionality. Synopsis: Macrophages undergo plasma membrane fusion and multinucleation to form osteoclasts, Langhans giant cells (LGCs) or foreign‐body giant cells (FBGCs). Cell fusion shapes context‐dependent activities of multinucleated macrophages at the expense of their identity. A single cytokine combined with M‐CSF can recap the typical morphological appearance of LGCs and FBGCs in vitro . Multinucleation causes down‐regulation of macrophage identity and enhanced lysosome‐dependent iron homeostasis. Multinucleated FBGCs show improved ability of phagocytosis, while osteoclasts maximize their mitochondrial activity. LGCs express B7‐H3 and can form granuloma‐like clusters in vitro . Abstract : Macrophages undergo plasma membrane fusion and multinucleation to form osteoclasts, Langhans giant cells (LGCs) or foreign‐body giant cells (FBGCs). Cell fusion shapes context‐dependent activities of multinucleated macrophages at the expense of their identity.